Response Of Red Cabbage (Brassica Oleracea Var. Capitata F. Rubra) To The Integrated Use Of Chemical Fertilizers, Biofertilizers And Boron (Applied Biological Research, 2014)
Present research work was conducted during 2009-2010 and 2010-2011 at  Horticulture Research Station, Mondouri, BCKVV, Nadia, West Bengal (India) to study the influence of integrated nutrient management using  chemical fertilizers, bio-fertilizers and micro-nutrient (boron) on growth,  yield and quality of red cabbage. The study revealed that growth  attributing characters viz., plant height and spread were higher (42.83 and  48.63 cm, respectively) with application of recommended NPK [120:60:60  kg ha-1] + Azotobacter chroococcum [@ 10 kg ha-1] + boron [@ 1 kg ha-1]. Higher head weight, head diameter and projected yield of 1375 g, 52.47 cm  and 37.02 tonnes ha-1, respectively, was achieved with the use of  recommended NPK + A. chroococcum + phosphate solublizing bacterium Bacillus polymyxa + boron. The dry matter, vitamin C, total sugar and  anthocyanin contents in red cabbage also improved when integrated  nutrient management was followed.
Keywords: Anthocyanin; Azotobacter chroococcum; Bacilus polymyxa; boron; chemical fertilizers; growth; red cabbage; yield